2014
DOI: 10.1021/am505985z
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Ionic Liquid–Biopolymer Electrolyte-Enabled Thin and Compact Magnesium–Air Batteries

Abstract: With the surge of interest in miniaturized implanted medical devices (IMDs), implantable power sources with small dimensions and biocompatibility are in high demand. Implanted battery/supercapacitor devices are commonly packaged within a case that occupies a large volume, making miniaturization difficult. In this study, we demonstrate a polymer electrolyte-enabled biocompatible magnesium-air battery device with a total thickness of approximately 300 μm. It consists of a biocompatible polypyrrole-para(toluene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 48 publications
(90 reference statements)
0
94
1
1
Order By: Relevance
“…This bio-battery exhibited slightly lower middle point voltages and capacities (1.29-1.06 V, 4.42-0.93 mA h cm -2 ) than the previously reported result with electrodeposited PPy-pTS cathode on SS mesh. [34] Nevertheless, it delivered a much higher stable voltage and specific capacity than those (0.4-0.7 V, 2.4 mA h cm -2 ) from recently reported biodegradable Mg-Mo battery. [9] We further investigated the rate capability ( Figure 5b) at the range of 5 to 100 µA cm -2 .…”
Section: Discharge Characteristics Of Mg-air Bio-batteries Composed Omentioning
confidence: 73%
“…This bio-battery exhibited slightly lower middle point voltages and capacities (1.29-1.06 V, 4.42-0.93 mA h cm -2 ) than the previously reported result with electrodeposited PPy-pTS cathode on SS mesh. [34] Nevertheless, it delivered a much higher stable voltage and specific capacity than those (0.4-0.7 V, 2.4 mA h cm -2 ) from recently reported biodegradable Mg-Mo battery. [9] We further investigated the rate capability ( Figure 5b) at the range of 5 to 100 µA cm -2 .…”
Section: Discharge Characteristics Of Mg-air Bio-batteries Composed Omentioning
confidence: 73%
“…The AC has high specific surface area of ≈ 3500 m . This is higher than the surface area of AC derived from durian shell [45]. The EDLC fabricated with the chitosanbased AC exhibited a capacitance of 338 F g scan rate.…”
Section: Chitosan In Electrical Double-layer Capacitors (Edlcs)mentioning
confidence: 83%
“…Chitosan is receiving a lot of attention as materials for bioelectrolytes and electrodes [45]. Membrane is the core component of polymer electrolyte fuel cells (PEFCs).…”
Section: Chitosan In Polymer Electrolyte Fuel Cells (Pefcs)mentioning
confidence: 99%
“…Coupled with biocompatible thin‐film cathode materials (e.g., platinum (Pt), copper (Cu), gold (Au), polypyrrole (PPy)), the constructed galvanic cells can offer electrical power through the electrochemical dissolution process of the active materials (Mg, Zn). Biofluids or biopolymer materials serves as the electrolyte, which circumvents the usage of hazardous solvents as that in general lithium‐ion battery . A miniaturized and flexible Mg–Cu and Zn–Cu galvanic cell, reported by Nadeau et al, is shown in Figure a .…”
Section: Energy Storage Systemsmentioning
confidence: 99%